2016
DOI: 10.1016/j.jid.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

From Hyperactive Connexin26 Hemichannels to Impairments in Epidermal Calcium Gradient and Permeability Barrier in the Keratitis-Ichthyosis-Deafness Syndrome

Abstract: The keratitis-ichthyosis-deafness (KID) syndrome is characterized by corneal, skin, and hearing abnormalities. KID has been linked to heterozygous dominant missense mutations in the GJB2 and GJB6 genes, encoding connexin26 and 30, respectively. In vitro evidence indicates that KID mutations lead to hyperactive (open) hemichannels, which in some cases is accompanied by abnormal function of gap junction channels. Transgenic mouse models expressing connexin26 KID mutations reproduce human phenotypes and present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 104 publications
3
50
0
1
Order By: Relevance
“…To our knowledge, our report is the first to detail the impact of this mutation on cellular integrity and provides evidence that disease progression is associated with necrotic cell death. We also show that the mutation has a trans‐dominant effect on the trafficking of Cx43 which, together with recent data for Cx26, suggest altered interaction with Cx43 may be indicative of severe Cx‐related skin disorders. Although the EKV‐P phenotype associated with this mutation is similar to other EKV‐P mutations reported, it is clear that the underlying mechanism attributed to the mutation is different, suggesting variable mechanisms of triggering the disease state and warrants further investigation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, our report is the first to detail the impact of this mutation on cellular integrity and provides evidence that disease progression is associated with necrotic cell death. We also show that the mutation has a trans‐dominant effect on the trafficking of Cx43 which, together with recent data for Cx26, suggest altered interaction with Cx43 may be indicative of severe Cx‐related skin disorders. Although the EKV‐P phenotype associated with this mutation is similar to other EKV‐P mutations reported, it is clear that the underlying mechanism attributed to the mutation is different, suggesting variable mechanisms of triggering the disease state and warrants further investigation.…”
Section: Discussionsupporting
confidence: 80%
“…Other mutations in Cx26, primarily associated with the amino‐terminal domain and the first part of first extracellular loop, are linked with KID syndrome. Recent studies indicate that a variety of Cx26 mutations have trans‐dominant effects on other epidermal connexins, including Cx43, inducing altered heteromeric channel function …”
Section: Discussionmentioning
confidence: 99%
“…Abnormal connection channels can influence the movement of potassium ions back into the endolymph, altering potassium concentration to the point of intoxication of the organ of Corti, ultimately resulting in sensorineural deafness (Lefebvre and Van De Water, 2000). To date, many studies have indicated that mutations in the gene GJB2 can interrupt the transmission of second messengers such as inositol trisphosphate and calcium ions between cells, and the former is known to play an important role in auditory physiology (Beltramello et al, 2005;García et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The gap junction beta 2 ( GJB2; NM_004004.5) gene of 2250 base pairs (bp) comprises two exons of which one exon, exon two, encodes the short 226 amino acid protein connexin (Cx) 26. To date, nine mutations (3) in Cx26 have been reported to cause KID syndrome in altogether approximately 100 cases (4). The dominant mutation GJB2 c.148G > A, p.Asp50Asn is the most common one (5–9).…”
Section: Introductionmentioning
confidence: 99%
“…1). The GJB2 gene is expressed in various tissues throughout the body but Cx26 has specifically been demonstrated to be co-expressed with other Cx proteins (Cx30, Cx31 and Cx43) in human epidermal keratinocytes and cochlea (4,12,13), i.e. tissues where the KID phenotype is expressed.…”
Section: Introductionmentioning
confidence: 99%